Timing Method for the Isoland Signalized Intersection Considering the Traffic Uncertainty - LING Mo;WU Zhen;GUO Jianhua (Nantong Daxue xuebao. Ziran kexue ban)
To deal with the stochastic nature of the traffic flow, a timing method for the isolated signalized intersection is proposed considering traffic uncertainty. First, seasonal autoregressive integrated moving average-generalized autoregressive conditional heteroskedasticity(SARIMA-GARCH) model is used to quantify the traffic uncertainty at each intersection. Then, based on the quantified uncertainty characteristic, the timing parameters is computed for the isolated intersection referring to the Webster method, obtaining the signal timing plan considering traffic uncertainty.Finally, taking an intersection in Nanjing as the example and using the real world traffic data, 17 timing plans are computed for the different traffic uncertainty levels. The performances of these timing plans are computed in Paramics software, validating the effectiveness of the proposed method.